Jak-stat signaling : From basics to disease - Müller, Mathias; Decker, Thomas (Springer Vienna, 2012)
JAK tyrosine kinases and STAT transcription factors constitute a signaling pathway, which is activated by cytokines. By activating gene transcription it regulates essential biological responses to environmental cues. The Jak-Stat pathway is involved in the regulation of cell development, differentiation, proliferation and apoptosis. Improper function may contribute to hematopoietic malignancies and cancer. This book provides comprehensive insights into the latest basic and clinical developments in the field. The first part reviews recent findings and new technologies pertaining to basics of Jak-Stat function. The second part describes the evolution of Jak-Stat signaling and the role of the pathway in invertebrate organisms. The third part focuses on Jak-Stat signaling in hematopoietic cells under both physiological and pathophysiological conditions. Finally, chapters in the fourth section describe the relationship of Jak-Stat signaling to various states of disease, particularly infection, leukemias and solid cancers. The book is intended for all scientists in molecular biology, biochemistry and cell biology dealing with biomedical issues.